Pembelajaran Contextual Teaching and Learning Materi Perbandingan pada Siswa MTs Negeri 2 Banda Aceh - Roslina Roslina; Rahmadi Rahmadi (Didaktik Matematika, 2016)
The purpose of this study was to determine the Contextual Teaching and Learning (CTL) for comparison material of students MTs Negeri 2 Banda Aceh can achieve mastery. The population was all seventh grade students of MTs Negeri 2 Banda Aceh while the sample was VII-4 grade of MTs Negeri 2 Banda Aceh. Collecting data in this study was conducted using tests shaped description of the material and the ratio obtained from the research carried out. Results obtained from tests processed using chi square test in order to determine the normality of the data. Then use the t-test (the test right) with to test the hypothesis. Based on these results indicate that thitung = 3.43 with df = 28, t distribution list indicates t = 1,701, so 3.43 1.701. It was thus clear that H0 refused and accept Ha, it can be concluded the results of hypothesis testing was by CTL comparative material on students MTs Negeri 2 Banda Aceh has reached completeness